2019
DOI: 10.1080/15236803.2019.1667185
|View full text |Cite
|
Sign up to set email alerts
|

Experiential philanthropy in China

Abstract: Experiential philanthropy is a form of service-learning where students are provided with money (generally from a foundation) to distribute to nonprofit organizations. The pedagogy is intended to teach students not only about philanthropy but also about how to evaluate philanthropic responses to social issues. In recent years, scholars have begun to explore how an experiential approach to the philanthropic process could result in a more philanthropically engaged and committed citizenry. This research has provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Literature consistently highlights the benefits of student philanthropy programmes (e.g., Ahmed & Olberding, 2007;McDonald et al, 2017;McDougle, 2022;Olberding, 2009Olberding, , 2012. Whilst most of the outcomes focus on US students, emerging evidence suggests that such programmes are transferable, as similar outcomes are experienced by students in China (Li et al, 2020). However, in the US certain students benefit more than others.…”
Section: Student Philanthropymentioning
confidence: 99%
“…Literature consistently highlights the benefits of student philanthropy programmes (e.g., Ahmed & Olberding, 2007;McDonald et al, 2017;McDougle, 2022;Olberding, 2009Olberding, , 2012. Whilst most of the outcomes focus on US students, emerging evidence suggests that such programmes are transferable, as similar outcomes are experienced by students in China (Li et al, 2020). However, in the US certain students benefit more than others.…”
Section: Student Philanthropymentioning
confidence: 99%
“…Certainly, research on experiential philanthropy has provided ample evidence of its efficacy as a pedagogic strategy to support student learning as well as the promotion of prosocial values and civic engagement (see Mao, 2021 for a review). It has even been demonstrated that the pedagogy has clear application to learning and engagement for students in applied fields such as business management (Campbell, 2014), public administration (Li et al, 2020), and social work (Olberding & Kim, 2021).…”
Section: Achieving a Responsive And Balanced Democracy Through Experi...mentioning
confidence: 99%
“…In fact, only one study to date has examined cross‐national variation in the short‐term effectiveness of experiential philanthropy on student outcomes. The findings of this study, which focused on two experiential philanthropy initiatives—one in the US and the other in China—indicated that similar to in the US, taking a course with an experiential philanthropy component increased Chinese students' awareness of social issues and provided them with a greater understanding of the role that nonprofit organizations can play in addressing these issues (Li et al, 2020). Moreover, the findings revealed that experiential philanthropy increased Chinese students' interest in philanthropic education, their intentions to participate in future philanthropic activities, and even their desire to choose a career in the nonprofit sector.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Mooney and Edwards (2001) have, therefore, suggested that "In its simplest form, service-learning entails student volunteering in the community for academic credit" (p. 181). In recent years, however, SLEs have also been designed to allow students opportunities to engage in the distribution of charitable funds-a pedagogical practice commonly referred to as experiential, or student, philanthropy (Li et al, 2019(Li et al, , 2020McDougle et al, 2017;Xu et al, 2019).…”
Section: Dominant Forms Of Service-learningmentioning
confidence: 99%